Antimicrobial Potential Of Medicinal Plant – Embelia Basal - GAYATRI S. KAMBLE; RASIKA C. TORANE; PRANAV C. CHANDRACHOOD; NIRMALA R. DESHPANDE; JYOTI P. SALVEKAR (International Journal of Pharma and Bio Sciences, 2011)
Embelia basal (R. & S.) A. DC is a shrub from family Myrsinaceae. Various species of Embelia are used in Ayurvedic system of medicines and mainly promoted as antibacterial as well as anthelmintic mediator. In order to search for antimicrobial activity of secondary metabolites, screening of different extracts of fruits of E. basal was carried out. Powdered fruit material was extracted using solvents of increasing polarity from non polar (n-hexane), semi-polar (Acetone) to polar (methanol). Extracts were analysed for their antimicrobial activity against six bacterial strains with two antifungal strains. The antimicrobial activity was determined by using disc diffusion method and inhibitions of microorganisms were correlated by using Streptomycin as a standard. Bacillus cereus, Staphylococcus aureus, pseudomonas aeruginosa was found to be more susceptible strains, in which methanol extract showed promising activities. Therefore this was selected for further investigation to determine its therapeutic potential and MIC calculation.